Total Phenolic Content and Antioxidant Activity of Three Flower Infusion Tea in Sakon Nakhon Province - Prathumtet, Jatuporn; Surasorn, Chakkrit; Paopa, Thipyamon (Journal of Health Science of Thailand, 2019)
Tea is a beverage that is appropriate choice for health care. It can eliminate free radical from endogenous and exogenous sources to promote illness preventing. The report recently found that various flowers have antioxidant property, leading to they play more attention on tea product. This research aimed to determined total phenolic content of three flower infusion tea compose of Clitoria ternatea L., Sesbania grandiflora (L.) Pers. and Bombax anceps Pierre. by using Folin-Ciocalteu colorimetric. The antioxidant activity of them was also investigated via DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity assay. The results found that types of flower infusion tea had an effect on total phenolic contents with significant differences (p<0.05). Flower infusion tea composing of Clitoria ternatea L. exhibited the highest total phenolic content with 33.16±0.54 mg GAE/g. It was higher than flower infusion tea from Bombax anceps Pierre. and Sesbania grandiflora (L.) Pers. Moreover, the results demonstrated that each flower infusion tea was significant differences (p<0.05) in antioxidant activity. Flower infusion tea composing of Clitoria ternatea L. represented the greatest %DPPH radical scavenging activity of 39.47±1.78 % and showed IC50 of 14.41±0.95 mg/ml. In conclusion, Clitoria ternatea L. is effectively antioxidant activity which its enrichment in total phenolic compounds. However, production process of this tea has to manage quality control of raw material. It is based on the audit and certification following GAP and GMP principle for standardization, national acceptable and commercial trade.